Towards computer investment in the automatic undestanding of the linguistic context –the phenomene of derivation is a model - Mssili, Warda (Milev Journal of Research and Studies, 2017)
Today humanity lives in the midst of a great technological revolution. the world come out of the area of informatics and entered the area of identifiers coincided with the emergence of anther net and its means is the computer that has moved from specialized laboratories and uses to sweep all areas of lifes. two interconnected worlds have created a common world connected by the Arabic character with a supernatural elegance and separate virtual world. the western character is the characteristics of the computer of a separate nature